ANALISIS PERBANDINGAN RETURN DAN RISK (STUDI PADA SAHAM SYARIAH DAN SAHAM KONVENSIONAL LQ45 PERIODE (2012-2016) - Muammar Khaddafi; Ferdiansyah Ferdiansyah (Department of Accounting, Faculty of Economics & Business, 2017)
This study aims to analyze the comparison of Return and Risk study in syariah Stocks and convensional stocks LQ45 Indeks in companies listed on the Indonesia Stock Exchange by using Purposive Sampling by comparing the rate of return and risk of these shares. The method used is the Independent Sample T-test and comparing the performance of mutual funds using the Jensen Test during the period 2012-2016, the results showed that there was no significant difference between the rate of return and risk of the Syariah Stock and Conventional Stock Index during the 2012-2016 period.